Rachel Carson's Silent spring - Goodwin, Neil.; McCullough, David G.; Chadwick, Alex, 1947-; Streep, Meryl; Peace River Films; WGBH Educational Foundation; WNET (Television station : New York, N.Y.); WGBH Video (Firm) ([South Burlington, VT] : WGBH Boston Video, 2008)
Witness the life of passionate biologist and environmentalist, Rachel Carson, and how she exposed the effects of the unregulated use of pesticides and herbicides by the federal government, and sparked a revolution in environmental policy.
Documentary.
Originally broadcast on the television program American experience in 1993.
Special features: DVD-ROM link to American Experience website; other products of interest.
Host: David McCullough.
Narrator: Alex Chadwick ; readings by Meryl Streep.
DVD, NTSC; region 1, full screen (4x3) presentation; Dolby Digital.
Keywords: Carson, Rachel, -- 1907-1964.; Biologists -- United States; Environmentalists -- United States -- Biography; Science writers -- United States; Pesticides -- Environmental aspects; Pesticides -- Toxicology; Pesticides and wildlife; Insect pests -- Biological control; Environmental health; Television programs; Biographical television programs